2011
DOI: 10.1039/c1ob06064c
|View full text |Cite
|
Sign up to set email alerts
|

Formate dehydrogenase - a biocatalyst with novel applications in organic chemistry

Abstract: In the field of industrial biocatalysis, formate dehydrogenase (FDH) is well established, in particular for its broad application in cofactor regeneration. Further applications have been limited by the enzyme's narrow range of substrates. These restrictions have been overcome now by the finding, that the enzyme is capable of selectively cleaving formic acid esters to the respective alcohol. Five homologous alkyl formates and phenyl formate as an aromatic ester were converted quantitatively by FDH from Candida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Butyl formate has a fruity, plum-like odor and corresponding taste and n-octyl formate has a fruity odor with a rose-orange note and a bitter flavor, refreshingly fruity green at low concentrations (Nurdock, 2010). Recently, formate esters such as octyl formate was used by formate dehydrogenase as a reactive solvent to regenerate NADH from NAD + (Frohlich et al, 2011;Janssen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Butyl formate has a fruity, plum-like odor and corresponding taste and n-octyl formate has a fruity odor with a rose-orange note and a bitter flavor, refreshingly fruity green at low concentrations (Nurdock, 2010). Recently, formate esters such as octyl formate was used by formate dehydrogenase as a reactive solvent to regenerate NADH from NAD + (Frohlich et al, 2011;Janssen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that organic solvents have effects on the enzyme activities [43,44]. The effects of organic solvents on the stability of cell-surface-displayed FDH were investigated (Table 3).…”
Section: Effect Of Organic Solvents On the Stability Of Cultures Exprmentioning
confidence: 99%
“…methyl, ethyl and propyl ester, had proven successful, we tested this variant also for siloxane 2. Advantageously, potential contributions of hydrolase activity, in concert with FDH-mediated oxidation of intermediately released formic acid, were shown to not interfere with the FDH-mediated deformylation of 2 [19]. Likewise a potential backward reaction through oxidation of isopropanol formed in the course of cofactor regeneration had no effect on the reaction, since the FDHmediated hydrogenation of CO 2 to formic acid firstly is too slow within the time scale of this reaction, and secondly it requires pressure > 5 MPa to produce detectable amounts within 10 h.…”
Section: The Last Percents To Complete Conversionmentioning
confidence: 99%